Effectiveness of Low-Deacetylation-Degree Chitosan as an Edible Coating for Apples, Tofu, and Tilapia Fillets - Ramadhan Wahyu; Tiftazani M. Haekal; Heri Suseno Sugeng; Septiyani Irawan Azizah; Astriyani Aisyah; Mahardika Vania; Sintia Armi Fuji; Silaban Rosella; Dewi Ghaisani Aatikah; Firdaus Zahrotul; Nasution Muheri Indra Aja; Butler Kyle; et al. (BIO Web of Conferences)
Food products like fish, fruits, and tofu are highly perishable, with quality degradation being a significant concern during storage. Chitosan, derived from shrimp waste, has potential as an edible coating to enhance shelf life. The degree of deacetylation (DD) is a key factor in chitosan's effectiveness, with high-DD chitosan (<80%) often requiring substantial resources for production. This study explores the use of low-DD chitosan (50%) as an edible coating for Nile tilapia fillets, apple slices, and tofu. Coatings were applied at intervals of 0, 6, 12, 18, and 24 hours, and samples were stored at room temperature (25 ± 2°C). Results show that low-DD chitosan significantly preserved the texture of Nile tilapia and tofu for up to 5 days (p>0.05). However, chitosan-coated apple slices exhibited increased browning, although oxidation was delayed compared to uncoated controls. These findings indicate that low-cost, low-DD chitosan could be an effective alternative for extending the shelf life of certain perishable foods without the need for high-purity chitosan.